The Application of Online Learning Assisted with Quizizz Educational Games in Learning Physics - Nirwana Nirwana; Ana Dhiqfaini Sultan; Khaeruddin Khaeruddin (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine student learning outcomes at SMA Negeri 21 Makassar before and after implementing online learning assisted by the educational game Quizizz. This research is a pre-experimental research. The total subjects of this study were 31 students. The data collection technique used was a multiple choice test with straight motion material. The collected data was then processed using descriptive statistical analysis and N-gain test analysis. The results showed that there was an increase in student learning outcomes after the application of online learning assisted by the educational game Quizizz from 13.42 to 23.98. The conclusion obtained is that online learning assisted by the educational game Quizizz is effective for improving student learning outcomes.